Does a Delay in Anterior Cruciate Ligament Reconstruction Increase the Incidence of Secondary Pathology in the Knee? A Systematic Review and Meta-Analysis. Issue 3 (May 2021) - Matthewson, Graeme; Kooner, Sahil; Rabbani, Rasheda; Gottschalk, Tania; Old, Jason; Abou-Setta, Ahmed M.; Zarychanski, Ryan; Leiter, Jeff; MacDonald, Peter
Abstract : Objective: Previous systematic reviews looking at timing of anterior cruciate ligament reconstruction (ACLR) examined the functional outcomes and range of motion; however, few have quantified the effect of timing of surgery on secondary pathology. The goal of this study was to analyze the effects of early ACLRs versus delayed ACLR on the incidence of meniscal and chondral lesions. Data Sources: We searched MEDLINE, EMBASE, and CINAHL on March 20, 2018, for randomized control trials (RCTs) that compared early and delayed ACLR in a skeletally mature population. Two reviewers independently identified trials, extracted trial-level data, performed risk-of-bias assessments using the Cochrane Risk of Bias tool, and evaluated the study methodology using the Detsky scale. A meta-analysis was performed using a random-effects model with the primary outcome being the total number of meniscal and chondral lesions per group. Results: Of 1887 citations identified from electronic and hand searches, we included 4 unique RCTs (303 patients). We considered early reconstruction as <3 weeks and delayed reconstruction as >4 weeks after injury. There was no evidence of a difference between early and late ACLR regarding the incidence of meniscal [relative risk (RR), 0.98; 95% confidence interval (CI), 0.74-1.29] or chondral lesions (RR, 0.88; 95% CI, 0.59-1.29), postoperative infection, graft rupture, functional outcomes, or range of motion. Conclusions: We found no evidence of benefit of early ACLR. Further studies may consider delaying surgery even further (eg, >3 months) to determine whether there are any real benefits to earlier reconstruction. Abstract : Supplemental Digital Content is Available in the Text.